2013
DOI: 10.1186/1423-0127-20-95
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin-induced cardioprotection against doxorubicin cytotoxicity

Abstract: BackgroundCancer has continually been the leading cause of death worldwide for decades. Thus, scientists have actively devoted themselves to studying cancer therapeutics. Doxorubicin is an efficient drug used in cancer therapy, but also produces reactive oxygen species (ROS) that induce severe cytotoxicity against heart cells. Quercetin, a plant-derived flavonoid, has been proven to contain potent antioxidant and anti-inflammatory properties. Thus, this in vitro study investigated whether quercetin can decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
47
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 34 publications
9
47
0
Order By: Relevance
“…The results are concordant with previous studies (22,23), which suggested that Quercetin glucosides in food products have been reported to exhibit chemopreventive activities. The lowest IC 50 value for onion extracts in cancer cell lines has been observed for those extracts with the highest presence of quercetin glucosides (22,23). This indicates that quercetin glucosides may be the most potent bioactive compound in onion extracts.…”
Section: Quercetin Glucoside Content % In Allium Species -----------supporting
confidence: 93%
See 1 more Smart Citation
“…The results are concordant with previous studies (22,23), which suggested that Quercetin glucosides in food products have been reported to exhibit chemopreventive activities. The lowest IC 50 value for onion extracts in cancer cell lines has been observed for those extracts with the highest presence of quercetin glucosides (22,23). This indicates that quercetin glucosides may be the most potent bioactive compound in onion extracts.…”
Section: Quercetin Glucoside Content % In Allium Species -----------supporting
confidence: 93%
“…Quercetins have been reported to exhibit anti-proliferative activity towards cancer cells in vitro and in vivo (15,20,21,23). Quercetin glucosides are considered to act as antioxidants in the genus Allium (22,23). The combination of quercetin glucosides may contribute to the anti-proliferative activity of onion extracts on cancer cells (20)(21)(22)(23).…”
Section: Quercetin Glucoside Content % In Allium Species -----------mentioning
confidence: 99%
“…It was shown that the liver has higher cytochrome-P450 reductase level than does cardiac tissue (Myers et al 1982). The semiquinone subsequently reacts with oxygen, iron, and hydrogen peroxide to produce ROS causing apoptosis and cell damage (Benchekroun et al 1993;Chen et al 2013). Therefore, oxidative stress induced in rat liver by ADR was found to be higher than in the controls in our current study.…”
Section: Discussionsupporting
confidence: 44%
“…*p \ 0.05 versus ADR. All data were expressed as mean ± SEM mitochondria electron transport system (Chen et al 2013) from mainly cytochrome-P450 reductase enzyme (Benchekroun et al 1993) which is important for the metabolism of both endogenous (e.g. lipids, steroids) and exogenous (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation